Smart road that warns its network manager when it begins cracking. Issue 3 (22nd February 2017) - Lenglet, Céline; Blanc, Juliette; Dubroca, Stéphane
Abstract : One of the components of the fifth generation road is its capacity to communicate with its network manager in order to improve maintenance. The aim of the experimental instrumentation presented in this study is to monitor the evolution of characteristic damage in mixed structures: nonvisible cracks rising from the hydraulic base towards the coated pavement surface. The objective of the sensors is to be able to anticipate damage before it reaches the surface. As temperature is also being measured, it is possible to use this data to communicate with users concerning the potential risk of ice forming on the road. The first measurements have been compared with a theoretical model of the structure, and the continuous acquisition of signals will enable the network manager to monitor the behaviour of the road.